Effects of centralizing meat inspection and food safety inspections in Finnish small-scale slaughterhouses. (August 2015) - Kotisalo, Niina; Luukkanen, Jenni; Fredriksson-Ahomaa, Maria; Lundén, Janne
Highlights: Meat inspection fees of small-scale slaughterhouses were significantly standardized. Cooperation between official veterinarians and food business operators was good. Food safety inspections did not take place in all small-scale slaughterhouses. Guidance given to official veterinarians requires improvement. Abstract: The official control of small-scale slaughterhouses has received criticism for inconsistent meat inspection fees and for the poor quality guidance and cooperation with food business operators (FBO) in Finland. The official control including both meat inspection (ante and post mortem) and food safety inspections (verification of FBO's self-inspection) of small-scale slaughterhouses was centralized from municipalities to the National Food Safety Authority (NFSA) in 2011 to address these perceived shortcomings. This study aimed to investigate the early effects of the centralization of meat inspection and food safety inspections, specifically the standardization of meat inspection fees and the quality of meat inspection services. In March all small-scale slaughterhouses ( n  = 52) received a questionnaire on the effects of centralizing meat inspection. We interviewed 12 small-scale slaughterhouses on site and the official veterinarians of ten of these small-scale slaughterhouses by phone. The results showed that introducing a meat inspection fee structure based on fixed hourly taxation that includes a fixed travel expense, can lead to more standardized fees. The variation in meat inspection fees after centralization was significantly smaller (Levene's test, p  = 0.013) than before. Moreover, after centralization, meat inspection fees and the number of slaughtered animal units per year showed no significant correlation. Meat inspection fees decreased for the majority of FBOs, which was expected because of the government subsidies the FBOs received. The majority of FBOs perceived the guidance as good both before and after centralization, and both FBOs and official veterinarians assessed their cooperation as good. The availability of official veterinarians to perform ante and post mortem inspections posed no problem for most FBOs. However, 50% of the FBOs interviewed stated that the official veterinarian had performed no food safety inspections after centralization, which can negatively impact food safety. The majority of the official veterinarians stated that the guidance they received from the NFSA improved after centralization, but they still urged more guidance on interpreting food safety requirements and performing food safety inspections.